2008
DOI: 10.1017/s1368980007000523
|View full text |Cite
|
Sign up to set email alerts
|

Increasing fruit and vegetable consumption: success of the Western Australian Go for 2&5®campaign

Abstract: Objective: The Western Australian Health Department's Go for 2&5 R campaign aimed to increase adults' awareness of the need to eat more fruit and vegetables and encourage increased consumption of one serving over five years. Design: The multi-strategy fruit and vegetable social marketing campaign, conducted from 2002 to 2005, included mass media advertising (television, radio, press and point-of-sale), public relations events, publications, a website (www.gofor2and5.com), and school and community activities. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 15 publications
8
155
0
1
Order By: Relevance
“…A study involving Western Australian adults showed that the campaign significantly increased knowledge about dietary recommendations of fruit and vegetables by 11?5 % and 23?5 %, respectively (19) . Children's fruit and vegetable knowledge may also be influenced by the Crunch&Sip TM campaign run in many Australian primary schools, implementing a break during morning lessons for children to eat fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving Western Australian adults showed that the campaign significantly increased knowledge about dietary recommendations of fruit and vegetables by 11?5 % and 23?5 %, respectively (19) . Children's fruit and vegetable knowledge may also be influenced by the Crunch&Sip TM campaign run in many Australian primary schools, implementing a break during morning lessons for children to eat fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent public health nutrition education programme in Australia is the Western Australian Health department's Go for 2&5 R campaign (2002)(2003)(2004)(2005) (16) . This multi-strategy fruit and vegetable campaign included media advertising and, importantly, an ongoing evaluation process.…”
mentioning
confidence: 99%
“…However, the media support for (15,16) . The National survey (15) was conducted over 3 months in 2005 via a series of pre-and post-campaign telephone surveys.…”
Section: Discussionmentioning
confidence: 99%